(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
The intersectionality of race, gender and decoloniality were the interfaces for the creation of the Worldwilde, Black, Woman performance in the process of the poetic experiment Ways to Be More. The aim of the article is to discuss the poetic and political powers of the Theater of the Oppressed in the process of creation, and decolonial ruptures of a black actress/performer during the height of the covid-19 pandemic. The procedures used were Image Theatre and Cop in the Head, by Augusto Boal, in a cartographic attitude, according to Virgínia Kastrup and Eduardo Passos, combined with the use of plants as teas and baths. The poetic experiment took place online, through the Zoom Platform.